Merging Dissemination and Knowledge Generation Participatory Art on Algorithmic Decision-Making - Blair, Kathryn; Hanson, Pil; Oehlberg, Lora (Peer Beyond Graduate Research Conference, 2025)
This paper is an invitation to transdisciplinary researchers to weave together public presentation and dissemination of work with their knowledge generation by gathering others’ impressions of their work. In my PhD research, I created participatory art installations about algorithmic decision-making and interview attendees to better understand others’ experiences with my work. I sought insight into the cognitive and aesthetic impressions visitors had during the exhibitions. I discuss my process of leveraging the exhibition site to generate knowledge with visitors. Understanding others’ experience informs my subsequent practice, deepening and enriching the resulting work. This enriched understanding also helps me gain insight into how researchers can better engage the public with techno-social issues.